The relationship between pornography use and sexual behaviours among at-risk HIV-negative men who have sex with men. - Eaton, Lisa A; Cain, Demetria N; Pope, Howard; Garcia, Jonathan; Cherry, Chauncey (Sexual health, 2012)
Although pornography is widely available and frequently used among many adults in the USA, little is known about the relationship between pornography and risk factors for HIV transmission among men who have sex with men.
Keywords: Adult; Attitude to Health; Erotica; Health Status; Homosexuality, Male; Humans; Male; Middle Aged; Risk Factors; Risk-Taking; Sexual Behavior; Sexual Partners; Unsafe Sex; Young Adult